Preventing Dental Issues from the Start: Oral Health Education for Kindergarten Students in Rural Communities - Sofia Lestari; Budi Santoso; Anita Sari (Journal of Community Action, 2026)
Oral health issues are a significant concern among children, especially in rural areas where access to dental care and education is limited. This study aims to evaluate the effectiveness of an oral health education program for kindergarten students in rural communities, focusing on preventing dental issues from an early age. The intervention consisted of interactive workshops, including demonstrations on brushing techniques, the importance of oral hygiene, and the impact of diet on dental health. The program was conducted in five rural kindergartens, reaching a total of 150 students. Pre- and post-intervention surveys assessed changes in students' knowledge and practices regarding oral hygiene. Results indicated a significant increase in both knowledge and self-reported brushing habits among the children. In addition, teachers and parents reported improved oral hygiene practices at home, with many parents adopting more active roles in ensuring proper dental care. This study underscores the importance of early intervention in oral health education and highlights the potential for sustainable improvements in children's oral hygiene behaviors in underserved rural areas. By preventing dental issues from the start, this program offers a cost-effective approach to improving long-term oral health outcomes in rural populations.